Twisted Light in a Single‐Crystal Fiber: Toward Undistorted Femtosecond Vortex Amplification. Issue 12 (12th September 2022) - Zhao, Yongguang; Zheng, Changsheng; Huang, Zixuan; Gao, Qinggang; Dong, Jifei; Tian, Kangzhen; Yang, Zhiyong; Chen, Weidong; Petrov, Valentin
Abstract: Intense femtosecond optical vortices with spatially structured amplitude and spiral phase front give rise to novel phenomena in light–matter interactions and strong‐field physics. However, current femtosecond vortex sources exhibit a poor power handling capability and amplification remains an open challenge due to a number of inherent technical difficulties. Here, it is demonstrated that a single‐crystal fiber laser amplifier is particularly well‐suited to directly amplify a femtosecond optical vortex without pulse stretching and compression in the time domain, while still maintaining the spatial properties associated with a clear central singularity and a spiral phase front, i.e., a well‐defined amount of orbital angular momentum (OAM).The optical nonlinearity experienced by such twisted light is verified to be substantially weaker compared to a fundamental mode beam where supercontinuum generation and spatial distortion are observed. The simple design and straightforward power scaling capability pave the way toward ultrahigh‐intensity femtosecond singular laser sources with an arbitrary topological charge. Such ultrafast OAM light sources are expected to help reveal complex physical phenomena in light–matter interactions and expand the applications to attoscience with X‐ray vortices, laser plasma acceleration, and micromachining. Abstract : A ingle‐crystal fiber (SCF) laser amplifier is demonstrated to be particularly well‐suited to directly amplify the femtosecond optical vortex without pulse stretching and compression in the time domain, while still maintaining its spatial properties. The simple design and straightforward power scaling capability pave the way toward ultrahigh‐intensity femtosecond singular laser sources with arbitrary topological charges.